Brix-acid ratio as an index of quality of tomato (Lycoserpicum esculentum Var. "Pope") - Hebron, Margaret C.; Alabastro, Estrella F. (1977)
The main objective of the study was to determine the range of color values of the raw material which would yield a high quality tomato sauce. The study consisted of three parts namely: (1) a follow-up of the changes in color, soluble solids, titratable acidity and Brix/acid ratio: (2) determination of the best range of Brix/acid ratio values that will yield the most acceptable product by correlating Brix/acid ratio values with color, consistency, flavor and general acceptability scores of the tomato sauce evaluation; and (3) translation of the best range of Brix/acid ratio values in terms of color of the raw materials which can be used as the basis of raw material control, by correlating Brix/acid ration values with the color determination values of the raw tomato. At three different stages of maturity, specifically on the fourth, sixth and eight days after harvest, the above physico-chemical properties were tested for changes during ripening. The results obtained were the following: (1) color changed from yellow orange to red orange to red with Munsell color notations of 7.5YR6/10, 10YR4/8 and 7.5R5/10, respectively; (2) percentage titratable acidity decreased from a range of 0.18% to 0.23% to a final range of 0.13 to 0.16% soluble solids increased from 3.8°Brix to 5.0°Brix; and (4) Brix/acid ratio increased from 11.11 to 38.79. A direct relationship between the Brix/acid ratio and each of the sensory qualities existed. The range of Brix/acid ratio values which gave the most acceptable product was from 30 to 40. An inverse relationship between the converted color values of the raw tomato and the Brix/acid ratio had been found. At the Brix/acid ratio range of 30 to 40, the sauce had converted color scores of 7.5 and 7.6 which had corresponding values of 7.5R4/10 and 7.5R5/10, respectively, in the Munsell color notation. The color description of the most acceptable sauce was red.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Tomatoes